PERENCANAAN STRUKTUR CITRA DREAM HOTEL SEMARANG - Anuntyo Pramuwicaksono; Dwina Maharani; Nuroji Nuroji; Parang Sabdono (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2014)
Design structure of Citra Dream Hotel Semarang by SNI 1726-2012 on this final report are designed inseismic zoning area of Semarang City, Central Java. The building are design with Structure Frame System method with configuration structure collapsethe System Bearer Special Moment (SRPMK). The structure frame system methodis are the configuration structure of the building with moment resisting frame consisting of beam and column. The configuration system of the Structural Frame System are consist of reinforced concrete structure. The building was firmly designed with some load combination such as dead load, live load, and earthquake. Design with The System Bearer Special Moment (SRPMK) election expected to be a high story building structure behave ductile therefor this building firm enough to be swayed by the earthquake that happened. This system is planned to use the concept of strong column weak beam, where the vertical elements of the structure (column) should be stronger than the horizontal elements of the structure (beam), to be plastically formed jointsfirst on the beam. The joints meeting of the beam-columnshould also be well designed to avoid collapse first. The analysis of the structure of high story building using SAP2000 v12 software help to design structural building. Software are used for helping to determine the fundamental period of the structure and the forces acting on the structure. In the configuration of the structure collapse the System Bearer Special Moment (SRPMK) fundamental structural period must be limited so that the structure is not very flexible. Results in the forces acting such a axial force, shear, tortion and moment on the structure are used to design the structure of high story building.